A fundação do Centro Brasileiro de Pesquisas Físicas e o início da pós-graduação em física no Rio de Janeiro - Pantaleo Junior, Modesto (2011)
This study looked at the Physics Post Graduation improvement in Brazil. The research was carried out by focusing on Fundação do Centro Brasileiro de Pesquisas Físicas / Brazilian Center for Physical Research once it counts on the pioneering Physics Post Graduation course. In this sense, this paper aimed at explaining the causes, the needs and the context which led to the Fundação do Centro Brasileiro de Pesquisas Físicas / Brazilian Center for Physical Research founding as well as its results. In order to accomplish with the objective proposed above, this research drew on different documents such as annual reports, newsletters, meeting minutes, resolutions, statutes, course catalogs, course registration books and balance sheets of the Fundação do Centro Brasileiro de Pesquisas Físicas / Brazilian Center for Physical Research and the University of Brazil, currently named as Universidade Federal do Rio de Janeiro / Rio de Janeiro University